Dying for a cup of tea. (19th October 2012) - Kormann, Raphaël; Languille, Eva; Amiot, Henri-Marc; Hertig, Alexandre
Abstract : We report the case of a 70-year-old woman who developed life-threatening arrhythmia as a result of acute and severe hypokalaemia, which she developed after consuming large quantities of a liquorice-rich herb tea. She had no previous heart condition. We also discuss the legislative discrepancy in both the USA and in Europe, whereby consumers are warned about the risk of chronic hypertension whenever they buy a product containing liquorice, yet the risk of hypokalaemia may not be mentioned at all.